Incorporating learning management system with social network sites to support online collaborative learning: Preliminary analysis - Razali, Sharifah Nadiyah; Shahbodin, Faaizah; Bakar, Norasiken; Hussin, Hanipah; Ahmad, Mohd Hafiez; Sulaiman, Normala (Springer, 2013)
In 21st Century Learning, students use educational technologies to apply knowledge to new situations, to analyse information, to collaborate, to solve problems, and to make decisions. Utilising emerging technologies to provide expanded learning opportunities is critical to the success of future generations. In this paper, the author aims to discover if the 21st century’s skills (collaboration, communication, problem solving, and critical thinking) can be discovered through integration of Learning Management System with Social Network Sites. In this preliminary study, two sets of questionnaires were distributed to 84 diploma students and 41 lecturers from Politeknik Ibrahim Sultan, Politeknik Merlimau, Politeknik Tuanku Syed Sirajuddin and Politeknik Sultan Idris Shah. This paper shares the preliminary findings on the perceptions of the students and lecturers on the use of Learning Management System, Social Network Sites and Collaborative Learning in the teaching and learning process. All collected data had been analyse using SPPS 19 software and the results of the study showed the existence of difficulties in communication and interaction in existing LMS and the need to assess students’ engagement in group projects. Incorporating LMS with Facebook to support Online Collaborative Learning as recommendation for future research is suggested.